Emotional inferences by pragmatics - Iza-Miqueleiz, Mauricio; Konstenius, A.; Ezquerro-Juanco, Francisco (My University, 2017)
It has for long been taken for granted that, along the course of reading a text, world knowledge is often required in order to establish coherent links between sentences (McKoon & Ratcliff 1992, Iza & Ezquerro 2000). The content grasped from a text turns out to be strongly dependent upon the reader’s additional knowledge that allows a coherent interpretation of the text as a whole. The world knowledge directing the inference may be of distinctive nature. Gygax et al. (2007) showed that mental models related to human action may be of a perceptual nature and may include behavioral as well as emotional elements. Gygax (2010), however, showed the unspecific nature of emotional inferences and the prevalence of behavioral elements in readers' mental models of emotions. Inferences are made in both directions; emotional inferences based on behavior and vice versa. Harris & de Rosnay (2002) and Pons et al. (2003) proved that different linguistic skills –in particular lexicon, syntax and semantics are closely related to emotion understanding. Iza & Konstenius (2010) showed that additional knowledge about social norms affects the participants’ prediction about would be inferred as the behavioral or emotional outcome of a given social situation. Syntactic and lexical abilities are the best predictors of emotion understanding, but making inferences is the only significant predictor of the most complex components (reflective dimension) of emotion comprehension in normal children. Recently, Farina et al. (2011) showed in a study that the relation between pragmatics and emotional inferences may not be so straight forward. Children with High Functioning Autism (HFA) and Asperger Syndrome (AS) present similar diagnostic profiles, characterized by satisfactory cognitive development, good phonological, syntactic and semantic competences, but poor pragmatic skills and socio-emotional competencies. After training in pragmatics a descriptive analyses showed the whole group to display a deficit in emotion comprehension, but high levels of pragmatic competences. This indicates a further need to study the relationship between emotion and inference in normal subjects too. We also suggest that while behavioral elements may indeed be of perceptual nature and the inference between emotion and behavior less culturally dependent especially when concerned with basic emotions -the inference concerned with social norms may be more complex and require elaborative inference. We suggest that in further studies a distinction between basic emotions and non basic emotions, social settings and non-social settings should be made. The cognitive models concerned with social action may be of more complex nature, but with recognizable features on lexical and syntactic levels.
Keywords: Emociones; Emotion; Inferencing; Pragmatics